Simulation of the Single Sign-On Method for Service Provider Applications: A Case Study of Bhayangkara University Surabaya - Sudrajat, Vicinthia Veren; Adityo, R.Dimas; Arizal, Arif (Universitas Medan Area, 2025)
The authentication system at Bhayangkara University Surabaya is still traditional, where users must have separate accounts for each service. This condition causes inefficiency, administrative burden, and security risks due to managing multiple credentials. This study aims to design and simulate a single authentication system based on Single Sign-On (SSO) to improve efficiency and ease of user access to campus digital services. The system was developed with an iterative approach using JSON Web Token (JWT) and RESTful API technology. The simulation was carried out by testing two applications, namely Identity Provider (IdP) and Service Provider (SP), which interact in a single authentication scenario. Three types of testing were carried out: (1) simulation of the login flow and SP access after authentication at the IdP, (2) compatibility testing between Android devices (multi-device), and (3) RESTful access performance testing, including response time, throughput, and token validity. The results show that the SSO system is able to centrally integrate campus services, accelerate authentication, and maintain access security. The average response time was recorded below 1.5 seconds, even when tested on 20 devices simultaneously. The implementation of SSO has been proven to improve operational efficiency and simplify user identity management. This system contributes to an improved user experience and can be replicated by other educational institutions with similar needs.